INVESTIGATION OF SIDOARJO MUD AS AN ADDITION IN FLY ASH BASED GEOPOLYMER CONCRETE - HASBI, AMIR FAUZI (2018)
Sidoarjo Mudflow (SM) is generated from the natural disasters of a volcanic eruption in Porong, Sidoarjo, East Java, Indonesia. It has been recorded that average amount of the eruption was about 180,000 m3 per day in 2007 and will continue to be active over 50 years from now.